Is the Scientific Literacy of the Philippines in the ICU? - Frank Angelo Pacala (ASEAN Journal of Science and Engineering Education, 2023)
This paper seeks to examine scientific literacy in the Philippines. This paper further explores the current state of scientific literacy in the Philippines by conducting a commentary literature review of existing literature from both local and international sources. It aims to develop a better understanding of how individuals inside the country view science, how the media interacts with science-related topics, and if any indicators are pointing to a lack of overall scientific education among younger generations. The view of this paper is that there is an utmost need for the improvement of scientific literacy among the people. There should be a comprehensive, transdisciplinary, and multilateral plan to combat fake news. Schools should focus on critical thinking skills. The anti-fake news ordinances of different localities should be strengthened and implemented properly. Media outlets should add more content that fosters scientific literacy and remove posts that are fake news in nature. Finally, the home should be the sanctum of truth and honesty.